Determining the Role of Pedestrian-Orientation, Concerning the Public Places: Improvement of Urban Social Capital Quality - Mohammad Moayedi; Reza Kheyroddin; Ismail Shieh (Salehan Institute of Higher Education, 2019)
Studying the status of urban social capital indicates that it is declining in contemporary cities. The experts in the field of social science have seriously warned on the consequences of this decline, by examining the components of social capital which is the result of forming norms of collective life and social interaction. In this regard, urbanization knowledge seeks to strengthen social capital through targeted interventions and efforts to improve the quality of urban life. Social interactions are significantly important factors contributing to the social capital and one of the most effective ways of realizing social interactions is making and developing of